Determination of water productivity of cassava in Ibadan, south western Nigeria - Aderemi, A. M.; Ewemoje, T. A.; Adedipe, J. O.; Oyewo, I. O.; Balogun, L. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The response of yields to the actual water (effective rainfall) used by cassava, was the main area of study of this project. A twenty data point (20 years) was processed using CROPWAT 8.0 model using fixed percentage (80%) method, the model was used to run the 20 years daily rainfall data collected from NIMET (Nigeria Meteorological Agency) Oyo State from 1994 to 2013 (20 years) while the cassava yield was collected from FAOSTAT website. The rainfall pattern for the annual period of cultivation for cassava was determined through the planting and dates of the crop. The results of the annual water productivity values show that there was a very low water productivity of 0.9kg/m3 in 2012 while 2013 recorded the highest water productivity of 2.2 kg/m3. The early planting of cassava after rainfall started in the month of March which contributed to the high yield recorded in 2010, 2011 and 2013. The poor performance of cassava in 2012 could be due to the following; the variety used, the soil type, the plant’s age at harvest, and the rainfall intensity and distribution during that particular year. The trend of the results was used to determine the alternative cost of water if the farm would be fully irrigated. It was gathered that 7000 litres of untreated water would be supplied to any farthest location at ₦12,000. Therefore, the cost was determined based on the yield and the water used annually.